The ater-group of the genus Apanteles Foerster (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of forty-eight new species - Liu, Zhen; He, Jun-Hua; Chen, Xue-Xin; Gupta, Ankita (Zootaxa, 2020)
The ater-group including subgroup eublemmae of genus Apanteles Foerster from China is revised, in which a total of 97 species are recorded and illustrated. Forty-eight new species are described and illustrated, i.e., A. albummacula Liu & Chen, sp. nov.; A. altus Liu & Chen, sp. nov.; A. ambultor Liu & Chen, sp. nov.; A. amotus Liu & Chen, sp. nov.; A. angustus Liu & Chen, sp. nov.; A. annosus Liu & Chen, sp. nov.; A. aphanofossa Liu & Chen, sp. nov.; A. aspersus Liu & Chen, sp. nov.; A. attenuator Liu & Chen, sp. nov.; A. bialtus Liu & Chen, sp. nov.; A. brevitempus Liu & Chen, sp. nov.; A. bulbus Liu & Chen, sp. nov.; A. cannabis Liu & Chen, sp. nov.; A. carssus Liu & Chen, sp. nov.; A. crassus Liu & Chen, sp. nov.; A. distributa Liu & Chen, sp. nov.; A. expansus Liu & Chen, sp. nov.; A. flavibasalis Liu & Chen, sp. nov.; A. fraxinus Liu & Chen, sp. nov.; A. fundum Liu & Chen, sp. nov.; A. fuscidentalis Liu & Chen, sp. nov.; A. jasmine Liu & Chen, sp. nov.; A. lateroglabris Liu & Chen, sp. nov.; A. limus Liu & Chen, sp. nov.; A. longicoxa Liu & Chen, sp. nov.; A. longidiscus Liu & Chen, sp. nov.; A. magastigma Liu & Chen, sp. nov.; A. muscosalis Liu & Chen, sp. nov.; A. ocellisublimus Liu & Chen, sp. nov.; A. plureseta Liu & Chen, sp. nov.; A. prominens Liu & Chen, sp. nov.; A. quadra Liu & Chen, sp. nov.; A. radocoxa Liu & Chen, sp. nov.; A. salsala Liu & Chen, sp. nov.; A. scrobiculatus Liu & Chen, sp. nov.; A. semicarinatus Liu & Chen, sp. nov.; A. stigmaium Liu & Chen, sp. nov.; A. tenuis Liu & Chen, sp. nov.; eublemmae-subgroup: A. alticella Liu & Chen, sp. nov.; A. aphanoiugum Liu & Chen, sp. nov.; A. cavitergita Liu & Chen, sp. nov.; A. impunctus Liu & Chen, sp. nov.; A. lineatella Liu & Chen, sp. nov.; A. longiala Liu & Chen, sp. nov.; A. palliditegula Liu & Chen, sp. nov.; A. rectala Liu & Chen, sp. nov.; A. rhombos Liu & Chen, sp. nov. and A. setosus Liu & Chen, sp. nov. Eleven newly recorded species are redescribed and illustrated, i.e., A. argiope Nixon, 1965; A. brunnistigma Abdinbekova, 1969; A. cerberus Nixon, 1965; A. chloris Nixon, 1965; A. cocotis Wilkinson, 1934; A. demades Nixon, 1965; A. medon Nixon, 1965; A. psenes Nixon, 1965; A. saravus Nixon, 1965; A. sartamus Nixon, 1965 and A. usipetes Nixon, 1965. Three new synonyms are proposed: A. chloris Nixon, 1965 = A. cornicula Chen & Song, 2004, A. cavatiptera Chen & Song, 2004 = A. glacilipes Song & Chen, 2004 = A. opacus (Ashmead, 1905). A key to Chinese species of the ater-group is provided.